PENDAMPINGAN PENGUATAN KEMAMPUAN POSTING KONTEN CREATOR PADA WEBSITE BAGI PENGURUS PONDOK PESANTREN DARUL ULUM UNGARAN - Ningsih, Dewi Handayani .U; Razak, Jeffri Alfa; Lusiana, Veronica; Noor Santi, Rina Candra (Intimas, 2023)
Digital content plays an important role for online users. Relevant, high-quality and interesting content will attract visitors' attention and support the business objectives or information you want to convey. Meanwhile, we know that a Content Management System (CMS) is a platform that has an intuitive user interface, which allows users to manage content, using text or visual editors. Web development for Islamic boarding schools is the process of creating and managing a website that has a primary focus on creating and presenting content that is relevant, informative and useful. Creator content in this context can include various types of material such as articles, videos, podcasts, infographics, religious studies, and various other forms of content. One of the activities that will be used as digital content is training and technical guidance on SInergi Bekam which is provided in the form of theory and practice directly as well as training and assistance in managing the Islamic boarding school website so that they are able to manage and operate the website via the website http://darululumungaran.com.